2012
DOI: 10.1371/journal.pone.0041929
|View full text |Cite
|
Sign up to set email alerts
|

Shared “Core” Areas between the Pain and Other Task-Related Networks

Abstract: The idea of a ‘pain matrix’ specifically devoted to the processing of nociceptive inputs has been challenged. Alternative views now propose that the activity of the primary and secondary somatosensory cortices (SI, SII), the insula and cingulate cortex may be related to a basic defensive system through which significant potentially dangerous events for the body's integrity are detected. By reviewing the role of the SI, SII, the cingulate and the insular cortices in the perception of nociceptive and tactile sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 68 publications
4
55
0
Order By: Relevance
“…AIns and dACC are activated by a range of tasks [9; 31; 85]. One view is that aIns mediates general interoception [27; 28], and dACC and aIns integrate salient external stimuli of all types with internal states [23]. A similar argument has been made for somatosensory regions [58].…”
Section: Discussionmentioning
confidence: 95%
“…AIns and dACC are activated by a range of tasks [9; 31; 85]. One view is that aIns mediates general interoception [27; 28], and dACC and aIns integrate salient external stimuli of all types with internal states [23]. A similar argument has been made for somatosensory regions [58].…”
Section: Discussionmentioning
confidence: 95%
“…Global patterns were estimated meta-analytically. Reproduced, with permission, from [113]. (G) RDMs based on spatial patterns of human event-related-potential amplitudes evoked by natural Images 101 ms after stimulus onset (top) and a model based on parameters of a Weibull fit to the spatially pooled distribution of local contrast measurements (bottom).…”
Section: Figurementioning
confidence: 99%
“…(F) RDM of whole-brain activity patterns during pain perception and other mental states. The RDM reveals the similarity in terms of global brain activity of eight mental states, suggesting shared recruitment of specialized brain regions in pain, emotion, interoception, and reward [113]. Yarkoni et al have presented a comprehensive meta-analytical framework for analyzing the discriminability of mental states from whole-brain activity patterns [114].…”
Section: Figurementioning
confidence: 99%
“…In addition, the ACC and insula, core regions of the SN, are always activated in respond to painful stimuli in migraine patients [27], [28]. One recent study has indicated that these areas are the most common brain regions that are active across a group of task-generated networks (including the network devoted to the processing of painful stimuli) [29], suggesting their importance in the detection and processing of salience information. Because of their noxious nature, nociceptive stimuli have intrinsically high saliency content [30].…”
Section: Introductionmentioning
confidence: 99%